Psoriasis/Psoriatic Arthritis Patients’ Long-term Treatment Patterns and Adherence to Systemic Treatments Monitoring Recommendations - Åsa Krantz; Juan Jesus Carrero; Yuanhang Yang; Lovisa Schalin; Josefin Lysell; Faizan Mazhar (Acta Dermato-Venereologica, 2023)
Limited information exists regarding treatment of patients with psoriasis/psoriatic arthritis in primary care. The aim of this study is to assess treatment patterns, adherence, persistence, and compliance in newly diagnosed patients with psoriasis/psoriatic arthritis from 2012 to 2018 in Stockholm, Sweden. In addition, laboratory monitoring before initiation of treatment and at recommended intervals was quantified for patients prescribed methotrexate or biologics. A total of 51,639 individuals were included, with 39% initiating treatment with topical corticosteroids and < 5% receiving systemic treatment within 6 months post-diagnosis. During a median (interquartile range) follow-up of 7 (4–8) years, 18% of patients received systemic treatments at some point. Overall, 5-year persistence rates were 32%, 45% and 19% for methotrexate, biologics, and other systemic treatments, respectively. Pre-initiation laboratory tests, as recommended by guidelines, were performed in approximately 70% and 62% of methotrexate and biologics users, respectively. Follow-up monitoring at recommended time intervals occurred in 14–20% and 31–33% of patients prescribed methotrexate and biologics, respectively. These findings highlight gaps in the pharmacological care of patients with psoriasis/psoriatic arthritis, including suboptimal adherence/persistence and inadequate laboratory monitoring.